Experimental and Numerical Investigation of the Effects of Transverse Reinforcement and Shear Span on Shear Capacity in Reinforced Concrete Cantilever Beams - Othman Majeed Abdullah; Aziz Ibrhim Abdulla; Wisam Amer Alus (Diyala Journal of Engineering Sciences, 2024)
This paper examines the impact of transverse reinforcement and shear span on the shear capacity of reinforced concrete (RC) cantilever beams through both experimental and numerical investigations. The experimental program included testing nine RC beams, each with dimensions of 200 × 300 × 1200 mm. The experimental results were compared with analytical predictions derived from empirical models based on the ACI 318-19 and British Standards (BS) codes.The findings reveal that stirrups significantly enhance shear strength, resulting in an increase in load-carrying capacity ranging from 16.6% to 32.7%, while ductility, as evidenced by increased rotation and curvature, improved by up to 260%. The stirrup spacings employed in the specimens were 75, 100, and 150 mm, with both reinforced and unreinforced specimens exhibiting shear failure.Increasing the shear span-to-depth ratio (a/d) from 2.44 to 3, while keeping the stirrup spacing at 75 mm, resulted in a 12.9% reduction in ultimate load capacity. When the stirrup spacing was increased to 100 mm, the ultimate load capacity experienced a further decline of 23.9%. All beams were analysed using the finite element software ABAQUS, with the finite element analysis (FEA) results closely aligning with the experimental outcomes, particularly in the load-deflection relationship and maximum load capacity. On average, the predicted ultimate load capacity from ABAQUS was 2.7% lower than the experimental results, while the average difference in deflection at ultimate loads between the experimental and numerical results was 7.54%.